New Conjugated Oligothiophenes Containing the Unique Arrangement of Internal Adjacent [All]‐S, S‐Oxygenated Thiophene Fragments. Issue 17 (27th March 2013) - Potash, Shay; Rozen, Shlomo
Abstract The quest for obtaining conjugated oligothiophene‐containing molecules with narrower HOMO–LUMO gaps and higher oxidation and reduction potentials is the subject of this study. Molecules containing the bithiophene tetraoxide (2) and the terthiophene hexaoxide (3) moieties were prepared and studied. They were obtained by transferring oxygen atoms to the corresponding dibromo oligothiophenes with the HOF⋅CH3CN complex and then cross‐coupling them with either thiophene‐ or acetylene tin derivatives. The photophysical and electrochemical studies of the products revealed that this particular class of mixed thiophenes is characterized by significantly smaller frontier orbital gaps and higher oxidation and reduction potentials compared with any other arrangement of oligothiophenes including various [all]‐S, S‐oxygenated thiophene derivatives.